(untitled) (Revista Tempo e Argumento, 2016)
This article looks at the history of left-wings in Colombia, framed within what was happening in the country, Latin America, and the world between 1958 and 2010. After specifying what we mean by “left-wings” and outlining their background in the first half of the 20th century, there is a panorama of five great moments of the period under study to reach the recent situation. The chronology favors the internal aspects of the history of Colombian left-wings, allowing us to appreciate their achievements and limitations framed into such a particular context as the Colombian one.